2010
DOI: 10.1016/j.neuron.2010.11.029
|View full text |Cite
|
Sign up to set email alerts
|

An Embedded Subnetwork of Highly Active Neurons in the Neocortex

Abstract: Unbiased methods to assess the firing activity of individual neurons in the neocortex have revealed that a large proportion of cells fire at extremely low rates (<0.1 Hz), both in their spontaneous and evoked activity. Thus, firing in neocortical networks appears to be dominated by a small population of highly active neurons. Here we use a fosGFP transgenic mouse to examine the properties of cells with a recent history of elevated activity. FosGFP-expressing layer 2/3 pyramidal cells fired at higher rates comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
197
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(238 citation statements)
references
References 47 publications
41
197
0
Order By: Relevance
“…On one hand, there may be a biological basis for this relationship: for example, experiments in cortical circuits show that highly active cells are more likely to be coupled (Yassin et al 2010). However, to examine whether temporal correlations are purely explained by higher firing, we looked at the relationship between resting firing rate and correlation probability.…”
Section: Mice Learn a Stimulus Discrimination Taskmentioning
confidence: 99%
“…On one hand, there may be a biological basis for this relationship: for example, experiments in cortical circuits show that highly active cells are more likely to be coupled (Yassin et al 2010). However, to examine whether temporal correlations are purely explained by higher firing, we looked at the relationship between resting firing rate and correlation probability.…”
Section: Mice Learn a Stimulus Discrimination Taskmentioning
confidence: 99%
“…11 A) of Crym-BAC-EGFP mice and investigated neuronal activity. Because extracellular electrophysiological recording typically has insufficient spatial resolution to discriminate neurons in adjacent repeating units and in vivo Ca 2ϩ imaging is difficult in layer V, we examined activity-induced c-Fos protein expression to investigate neuronal activity (Sagar et al, 1988;Kaczmarek and Chaudhuri, 1997;Farivar et al, 2004;Yassin et al, 2010) (Fig. 11 B, C).…”
Section: Correlated C-fos Expression In Single Repeating Units Under mentioning
confidence: 99%
“…Although c-Fos expression is generally well correlated with neuronal activity (Sagar et al, 1988;Kaczmarek and Chaudhuri, 1997;Farivar et al, 2004;Yassin et al, 2010), it will be necessary in the future to determine how precisely c-Fos expression correlates with action potentials under our experimental conditions. Nevertheless, the correlated c-Fos expression suggests that neurons in single repeating units have similar neuronal activity, and therefore have related functions.…”
Section: Relationship To Previously Characterized Neocortical Structuresmentioning
confidence: 99%
“…Despite these findings, it is difficult to predict the overall level of AMPAR function in Arcexpressing neurons, which is influenced by a variety of experience-regulated factors other than Arc. Those factors may promote increases in AMPAR function and counteract Arc's effects (Yassin et al, 2010;Jakkamsetti et al, 2013). In our own experiments, we found that while AMPAR function is altered in HOM mice compared with HET mice, the distribution of AMPAR current levels between GFPϩ and GFPϪ neurons from HET and HOM mice does not correlate with that of persistent firing patterns.…”
mentioning
confidence: 99%